Antiarrhythmic gene therapy: will biologics replace catheters, drugs and devices? - Lugenbiel, Patrick; Schweizer, Patrick Alexander; Katus, Hugo; Thomas, Dierk (European journal of pharmacology, 2016)
The clinical management of heart rhythm disorders still constitutes a major challenge. The development of alternatives to current approaches is of significant interest in order to establish more effective therapies that increase quality of life and reduce symptoms and hospitalizations. Over the past two decades the mechanistic understanding of pathophysiological pathways underlying cardiac arrhythmias has advanced profoundly, opening up novel avenues for mechanism-based therapeutic approaches. In particular, gene therapy offers greater selectivity than small molecule-based or interventional treatment. The gene of interest is packaged into viral or non-viral carriers and delivered to the target area via direct injection or using catheter-based techniques, providing the advantage of site-restricted action in contrast to systemic application of drugs. This work summarizes the current knowledge on mechanistic background, application strategies, and preclinical outcome of antiarrhythmic gene therapy for atrial fibrillation, ventricular tachycardia, and modulation of sinus node function.
Gesehen am 03.06.2019